Are small-scale poultry farmers aware of aflatoxin contaminants in feed in Oyo State, Nigeria? (2022)
Aflatoxins, feed contaminants formed by certain moulds occur naturally as feed and food impurities and have toxic consequences on both animals and humans. Earlier studies on aflatoxins in Nigeria did not consider small-scale poultry farmers’ awareness of feed contamination. Thus, this study examined the level of awareness of flatoxins in poultry feed and its determinants. Descriptive Statistics and the Logistic Regression Model were the analytical tools employed to analyse data collected from field survey in 2019. One-third of the farmers were aware of aflatoxins in feed which depicts that the level of awareness of aflatoxin in feed by the poultry farmers in the study area is low. Years of education, primary occupation, farm-scale, years of farming experience, access to information from research institutions, and membership in cooperative societies were among the key determinants of the awareness of aflatoxin in feed by the farmers. Efforts should be geared towards increasing the level of awareness of the farmers on the highly toxic contaminant even when fed to poultry at non-fatal levels. Agricultural information highlighting the detrimental consequences of aflatoxin on the health and productivity of poultry and how to minimize aflatoxin contamination in feed should be made more accessible to all farmers.